Firemní kultura jako cesta k získání zákazníka u společnosti Symeco s.r.o. - Kadlecová, Pavla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Bakalářská práce se zabývá posouzením současného stavu firemní kultury, jako cesty k získání zákazníka ve společnosti SYMECO s.r.o., návrhem a výběrem vhodné formy propagace společnosti. Specifikuje firemní kulturu a srovnává teoretické poznatky se skutečností. Výběr formy propagace byl uskutečněn mimo jiné na základě analýzy SWOT.

This thesis deals with assessing the current state of corporate culture as a way to win customer at SYMECO s.r.o., with proposal and selection of appropriate forms of promotion. Specifies the corporate culture, and compares theoretical knowledge with the facts. The choice of form of promotion was carried among others on the basis of a SWOT analysis.
Corporate Culture as a Way to Win Customers at Symeco s.r.o.
Keywords: Firemní kultura; společnost; propagace; marketing; Company culture; company; promotion; marketing